The Flooding Hydrology of Mackenzie Delta Lakes near Inuvik, N.W.T., Canada - Marsh, P.; Hey, M. (ARCTIC, 1989)
The hydrologic regime of lakes in the Mackenzie Delta is controlled primarily by lake sill elevations and water levels in the Mackenzie River distributary channels. The resulting variations in lake regime have important effects on the water, sediment, and nutrient balance of delta lakes, and therefore on the biologic regime of each lake. Analysis of 12-25 years of Mackenzie River East Channel water levels allowed the documentation of the relationship between flooding regime and sill elevation for lakes in the study area near Inuvik, N.W.T. These data showed that in this portion of the delta, the timing of the spring rise in water levels is very consistent, with peak levels, for example, occurring on 3 June with a standard deviation of only 4 days. The magnitude of the spring flood varies greatly from year to year, and as a result only 67% of lakes in the study area flood annually in the spring, while the remaining lakes have a flood frequency of greater than 1 year and less than 4 years. Since the mean summer flood peak of 2.777 m asl is considerably lower than the mean spring peak of 5.636 m asl, summer lake flooding is not as extensive, with only 20% of lakes receiving floodwater annually during the summer. By late summer, water levels drop to 1.5 m asl annually, cutting off approximately 88% of lakes from the Mackenzie River. These data on the return period of lake flooding allowed the classification system described by Mackay (1963) to be quantified. The no-, low- and high-closure lakes were found to represent 12, 55, and 33% respectively of all lakes in the study area. Variations in the hydrologic regime of the Mackenzie River could occur in the future due to hydro-electric development, climate change, or rising sea level. Even small changes in Mackenzie River levels could result in a significant modification to the hydrologic regime of delta lakes. The effects on the viability of these lakes, or their chemical and nutrient balances, are not well known.Key words: Mackenzie River, Mackenzie Delta, hydrology, ...